A systematic review of golf warm-ups behaviors, injury, and performance - Ehlert, A.; Wilson, B. P. (The Journal of Strength and Conditioning Research, 2019)
Previous literature has demonstrated that warm-ups have the potential to increase physical performance and reduce risk of injury. Warm-ups before golf may have a similar result, but a systematic evaluation of their effects in golf is currently lacking. Three electronic databases (PubMed, SPORTDiscus, and Web of Science) were systematically searched to address 3 primary research questions: (a) What are the current warm-up behaviors of golfers?; (b) Is there an association between warm-up behaviors and golf-related injury?; and (c) What are the effects of various warm-up protocols on measures of golf performance? Twenty-three studies (9 observational and 14 experimental) were identified that included data on warm-ups before golf participation. Overall, the current data suggest that many golfers either do not warm-up regularly or perform a warm-up that is short in duration. Studies on the association between warm-up behaviors and golf-related injury were mixed and inconclusive. Experimental studies suggest that a variety of warm-up methods may be beneficial for golf performance. Specifically, dynamic warm-ups and those with resistance exercise tended to enhance measures of performance, whereas static stretching was inferior to other methods and potentially detrimental to performance. Overall, the results of this systematic review suggest that various warm-up protocols (with the exception of static stretching) may enhance golf performance, but observational data suggest many golfers do not regularly perform them. More data are needed on the warm-up behaviors of competitive golfers, the impact of warm-up behaviors on golf-related injury, and to further identify effective warm-up methods for enhancing golf performance.